Sleep Promotes Cortical Response Potentiation Following Visual Experience - Aton, Sara J. (Associated Professional Sleep Societies, LLC, 2014)
STUDY OBJECTIVES: Sleep has been hypothesized to globally reduce synaptic strength. However, recent findings suggest that in the context of learning and memory consolidation, sleep may promote synaptic potentiation. We tested the requirement for sleep in a naturally occurring form of experience-dependent synaptic potentiation in the adult mouse visual cortex (V1), which is initiated by patterned visual experience. DESIGN: Visual responses were recorded in individual V1 neurons before and after presentation of an oriented grating stimulus, and after subsequent sleep or sleep deprivation. MEASUREMENTS AND RESULTS: We find that V1 response potentiation—associated with a shift in orientation preference in favor of the presented stimulus—occurs only after sleep and only during the entrained circadian sleep phase, and is blocked by sleep deprivation. Induction of plasticity following stimulus presentation is associated with an increase in principal neuron firing in V1, which is present in all behavioral states and occurs regardless of time of day. Sleep dependent potentiation is proportional to phase-locking of neuronal activity with thalamocortical spindle oscillations. CONCLUSIONS: Our results suggest that sleep can promote cortical synaptic potentiation in vivo, and that this potentiation may be mediated by slow wave sleep spindles. CITATION: Aton SJ, Suresh A, Broussard C, Frank MG. Sleep promotes cortical response potentiation following visual experience. SLEEP 2014;37(7):1163-1170.